Bees provide pollination service to Campsis radicans (Bignoniaceae), a primarily ornithophilous trumpet flowering vine. (12th September 2020) - Van Nest, Byron N.; Edge, Andrea A.; Feathers, Michael V.; Worley, Anne C.; Moore, Darrell
Abstract : Pollination syndromes refer to stereotyped floral characteristics (flower colour, shape, etc.) that are associated with a functional group of pollinators (bee, bird, etc.). The trumpet creeper Campsis radicans, endemic to the southeast and mid‐west United States, has been assigned to the hummingbird‐pollination syndrome, due mainly to its red, trumpet‐shaped flowers. Previous studies demonstrated that the ruby‐throated hummingbird Archilochus colubris is C. radicans ' primary pollinator, but anecdotal data suggest various bee species may provide pollination service when hummingbirds are absent. This study characterised C. radicans nectar volume and concentration by time of day. Nectar volume was suitable for hummingbirds, but concentration was higher than typical hummingbird‐pollinated plants (∼20% w/w); at ∼30% w/w, it approached the concentration expected in bee‐pollinated plants (∼50% w/w). We also found substantial amounts of nectar at night. Two C. radicans populations received virtually no hummingbird visits, but the number of bees were markedly higher than in the populations previously described. Interestingly, there were no night‐time visitors despite the large quantity of nocturnal nectar. Based on previously published pollen delivery per visit by various species, this study estimated that cumulative deposition by bees routinely reached pollen deposition thresholds for setting fruit in C. radicans . They are, unequivocally, the predominant pollinators in these populations, thus providing pollination service in the absence of hummingbirds. These results highlight C. radicans as a food source for native bees and add to the understanding of how floral phenotypes can facilitate pollination by disparate functional groups. Abstract : Campsis radicans is typically considered ornithophilous due to its large, red, trumpet‐shaped flowers; however, in populations in northeast Tennessee, U.S.A., hummingbirds were virtually absent. Nonetheless, the plant regularly sets fruit. Other floral traits (nectar concentration, visual nectar guides) suggest C. radicans is mixed with respect to pollination syndromes. The collective activity of bees, particularly Halictidae and Bombus spp., appeared to transfer sufficient pollen for fruit and seed set, despite high pollen consumption by halictids.